PEGylation, an approach for improving the pulmonary delivery of biopharmaceuticals. (September 2017) - Guichard, M-J.; Leal, T.; Vanbever, R.
Abstract: More and more therapeutic proteins are developed for an administration by inhalation to treat respiratory diseases. PEGylation is an interesting approach for sustaining the residence time of these biopharmaceuticals in the lungs and thereby decrease the frequency of administration and the daily burden of inhalation therapies. Several PEGylated proteins have been delivered to the lungs in rodents and shown to be retained in the respiratory tract for longer periods than unconjugated counterparts. Mechanisms involved in their pulmonary retention might include increased molecular size, mucoadhesion, enhanced proteolytic resistance and escape from the uptake by alveolar macrophages. Pulmonary delivery of PEGylated peptides and proteins is also interesting as a non-invasive route of administration of long-acting biopharmaceuticals to the bloodstream. However, PEGylation decreases the systemic absorption of the compounds, especially when the PEG size is large. This review presents the recent work carried out on the pulmonary delivery of PEGylated biopharmaceuticals, the factors affecting residence time in the lungs and systemic absorption as well as the safety of the approach in preclinical studies. Graphical abstract: